2003
DOI: 10.1100/tsw.2003.85
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Residues in Canned Foods, Fruits, and Vegetables: The Application of Supercritical Fluid Extraction and Chromatographic Techniques in the Analysis

Abstract: Multiple pesticide residues have been observed in some samples of canned foods, frozen vegetables, and fruit jam, which put the health of the consumers at risk of adverse effects. It is quite apparent that such a state of affairs calls for the need of more accurate, cost-effective, and rapid analytical techniques capable of detecting the minimum concentrations of the multiple pesticide residues. The aims of this paper were first, to determine the effectiveness of the use of Supercritical Fluid Extraction (SFE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…According to the detected pesticides in and/or on the non leafy vegetables ( Table 2) involved in this study, it was observed that total numbers of the detected compounds were found in cold pepper followed by cucumber, hot pepper, potato, okra, bean, carrot, squash, egg plant, cultivation tomato, green house tomato, onions, and cauli�ower. e total number of the detected compounds in such leafy vegetables in this study was 10,9,8,8,8,8,8,7,7,5,4,3, and 1 compound, respectively. e data tabulated in Table 2 also showed the detected amounts of pesticide residues in non leafy vegetables could be ranked in descending order as follows: cold pepper, egg plant, carrot, cucumber, potato, hot pepper, cultivation tomato, squash, bean, okra, onions, cauli�ower, and green house tomato which represent the lower non leafy vegetable contained pesticide residues.…”
Section: Pesticide Residues In Nonleafy Vegetables During Thementioning
confidence: 66%
See 2 more Smart Citations
“…According to the detected pesticides in and/or on the non leafy vegetables ( Table 2) involved in this study, it was observed that total numbers of the detected compounds were found in cold pepper followed by cucumber, hot pepper, potato, okra, bean, carrot, squash, egg plant, cultivation tomato, green house tomato, onions, and cauli�ower. e total number of the detected compounds in such leafy vegetables in this study was 10,9,8,8,8,8,8,7,7,5,4,3, and 1 compound, respectively. e data tabulated in Table 2 also showed the detected amounts of pesticide residues in non leafy vegetables could be ranked in descending order as follows: cold pepper, egg plant, carrot, cucumber, potato, hot pepper, cultivation tomato, squash, bean, okra, onions, cauli�ower, and green house tomato which represent the lower non leafy vegetable contained pesticide residues.…”
Section: Pesticide Residues In Nonleafy Vegetables During Thementioning
confidence: 66%
“…e frequency of the detected pesticide residues was calculated in the analyzed non leafy vegetables, it was found that the most frequent compounds was permethrin followed by deltamethrin and linden, endosulfan, chlordane, linuron, dimethoate, phosmet, and carbaryl. In terms of �gures, the frequencies for these pesticides were 11,8,6,5,5,5,4, and 4, respectively. e other detected compounds were frequented from three to one time.…”
Section: Pesticide Residues In Nonleafy Vegetables During Thementioning
confidence: 99%
See 1 more Smart Citation
“…Supercritical fluid extraction can be tailored to the polarity of the solute of interest by changing the temperature and pressure of the extraction process for removal of pesticides residue from foods (Camel 1998). Estimation of these residual pesticides, herbicides and fungicides can be done by SFC (El-Saeid 2003). High value nutraceuticals can be enriched by fractionation through a two-step process consisting of supercritical fluid extraction and supercritical fluid chromatography Montanari et al 1996).…”
Section: Special Applicationsmentioning
confidence: 99%
“…developed an SFC–PDA method for atrazine in standard solutions . Also El‐Saeid used SFC–PDA for the determination of pesticide residues in canned foods, fruits, and vegetables . Bicchi et al.…”
Section: Introductionmentioning
confidence: 99%